Multifunctional Agricultural Policies: Pathways towards Sustainable Rural Development? - Mölders, Tanja (The International Journal of Sociology of Agriculture and Food, 2014)
The article starts from two assumptions: it understands global shocks as both social-ecological crises and, as a way out of them, offering sustainable development. Sustainability in the area of agricultural policies and rural development is inherently connected to multifunctionality, a leading principle of the Common Agricultural Policy (CAP).To make a real estimate of the contribution of multifunctional agricultural policies to sustainable rural development, this article argues that the possibilities need to be discussed of integrating different and partly contradictory rural development goals and objectives. An understanding of sustainable development is therefore developed whose purpose is not to unify the un-unifiable, but which asks for sustainable economies that preserve and regenerate society’s ecological and social functions.This is the heuristic background against which two CAP documents are analysed: the rural development regulation EFRAD, on the one hand, and the Community Strategic Guidelines for Rural Development on the other. The analysis demonstrates the multiple biases and internal contradictions proposed that make it hard to identify pathways towards sustainable development.As a result, two interpretations of multifunctional agricultural policies are generated: adaptation sees multifunctional agricultural policies from a critical perspective, and argues that the economic mechanisms and strategies that have led to the crises in rural areas are reproduced rather than reflected upon. Transformation introduces a visionary perspective in its argument that multifunctional agricultural policies lead to a changed and extended perspective, so that (re)productive economies can be developed and established, and a transformation process initiated towards sustainable rural development.